PENGARUH JAMINAN PERLINDUNGAN DANA DEPOSITO DAN SIMPANAN BERENCANA TERHADAP MINAT NASABAH PADA BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU NGUNUT TULUNGAGUNG: USWATUN NA'IMAH - na'imah, uswatun (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2019)
This research is backed by a weak understanding of the society of its rights as a depository of funds is still low. This study was conducted to provide information to the Bank of sharia funds on the financial guarantee that they have stored in Bank Syariah Mandiri. In this study using quantitative approaches with associative types, the scale used is the Likert scale. Sampling using random sampling techniques. To analyze such data researchers use SPSS program analysis version 16.0 with multiple regression analysis. The result of this study is (1) The Banking law has no significant effect on the interest of customers in Bank Syariah Mandiri KCP Ngunut Tulungagung, (2) Bank Indonesia supervision affects not significant to the interest of customers in Bank Syariah Mandiri KCP Ngunut Tulungagung. (3) Consumer protection law is not significant to the interest of customers in Bank Syariah Mandiri KCP Ngunut Tulungagung, (4) Guarantor Guarantee Board is positive and significant influence on customer interest in Bank Syariah Mandiri KCP Ngunut Tulungagung (5) The assurance of banking law, the supervision of Bank Indonesia, the guarantee of consumer protection law, the guarantee of deposit guarantors together positively and significantly influence the customer interest in the Bank Syariah Mandiri KCP in Tulungagung